A review on the landfill leachate treatment technologies and application prospects of three-dimensional electrode technology. (March 2022) - Yu, Dayang; Pei, Yuansheng; Ji, Zehua; He, Xudan; Yao, Zhiliang
Abstract: With the expansion of urbanisation, the total amount of solid waste produced by urban residents has been increasing, and the problem of municipal solid waste disposal has also been aggravated. Landfill leachate treatment technologies could be divided into three categories: biological, physical and advanced oxidation treatment technology. Among them, advanced oxidation treatment technology has a good effect on the treatment of landfill leachate with little secondary pollution and has excellent application potential. Three-dimensional (3D) electrode technology, as a new type of advanced oxidation technology, could remove refractory pollutants in water and has attracted considerable attention. This article aims to (1) compare existing landfill leachate treatment technologies, (2) summarise 3D electrode technology application scenarios, (3) discuss the advantages of 3D electrode technology in landfill leachate treatment and (4) look ahead the future directions of 3D electrode technology in landfill leachate treatment. We hope that this article will be helpful to researchers who are interested in the field of landfill leachate treatment. Graphical abstract: Image 1 Highlights: Compared the existing landfill leachate treatment technologies. Summarized 3D electrode technology application scenarios. Discussed the advantages of 3D electrode in landfill leachate treatment. Looked ahead the future direction of 3D electrode in landfill leachate treatment.